MODERN PRINCIPLES OF ORGANIZATION OF INDEPENDENT WORK OF STUDENTS IN THE STUDY OF HISTOLOGY, CYTOLOGY AND EMBRYOLOGY - Федосєєва, О.В. (World of Medicine and Biology, 2015)
Independent work of students in the modern aspect - is the main form of organization of education including types of individual and collective studying activities and take into account the individual characteristics and cognitive abilities of students, under the guidance of the teacher, but without his direct involvement. The article presents the basic principles and methods of organization of independent work of students at the Department of Histology, Cytology and Embryology ZSMU in terms of credit-modular educational system.
Keywords: independent work; histology; credit-modular system